Reporting clinical research: Guidance to encourage accurate and transparent research reporting - Simera, I; Kirtley, S; Altman, D (2012)
To encourage accurate, complete, and transparent reporting of research studies we provide a brief overview of generic guidelines for reporting the main types of clinical research: randomised trials, observational studies in epidemiology, and systematic reviews. These and many other guidelines developed to help authors to achieve the highest standards in their research publications are available on the EQUATOR (Enhancing the Quality and Transparency of Health Research) Network website (www.equator-network.org).